SEKOLAH MENENGAH KEJURUAN DESAIN ANIMASI DI BANJARBARU - Amalia, Julia Rizky; Wastuty, Prima Widia (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Animation is a sub-sector of the creative industry that has promising business opportunities and is able to absorb a lot of creative labor. The increasing number of animation creators in Indonesia shows the increasing demand for animated films, unfortunately the quality of animators has not been able to compete internationally due to inadequate infrastructure and low education. The government also encourages the development of the animation industry by opening vocational education, where the Animation Vocational School can become a special forum for learning activities in the field of animation technology which aims to improve Human Resources (HR). The Interactive Space theme offers problem-solving for Animated Vocational Schools which have an interactive platform. The method used is to create a place to stimulate ideas. Like a waiting room which can be a collaborative space for discussion and relaxation.